Edma Grows Up: Ten Years of Early Childhood Mathematics Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
These days, we are celebrating the 10th anniversary of Edma's founding, and it is time to change the direction of the journal, to give it a new impetus. Next, I will briefly review the founding ideas, and the most relevant milestones, in the history of Edma, a project born in 2012, dedicated to promoting Early Childhood Mathematics Education. I will try to provide a vision that emphasize the "successes" that the journal has had in these 10 years, its "failures", and the challenges for the future.
Keywords: Early Childhood Education; Mathematics Education